1998
DOI: 10.1046/j.1464-410x.1998.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of quality of life in patients with continent urinary diversions after cystectomy

Abstract: Objective  To determine the long‐term results and assess the quality of life in patients with continent urinary diversions after cystectomy. Patients and methods  Eighty‐six consecutive patients who received a continent urinary diversion from 1988 to 1994 at the Vancouver Hospital and Health Sciences Center were evaluated. The evaluation comprised a review of their hospital charts and clinic visits at 3 months and then yearly. Quality of life issues were assessed using a postal questionnaire pertaining to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…In the present series, the operation did not have any bad in uence on our patients concerning their interaction with friends and hobbies. Continent urostomy can be rated as a real alternative in terms of quality of life for patients who require urinary diversion for any reason (1,12,18). In the present series, all patients appreciated the operation and felt free to lead an acceptable life.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present series, the operation did not have any bad in uence on our patients concerning their interaction with friends and hobbies. Continent urostomy can be rated as a real alternative in terms of quality of life for patients who require urinary diversion for any reason (1,12,18). In the present series, all patients appreciated the operation and felt free to lead an acceptable life.…”
Section: Discussionmentioning
confidence: 58%
“…Continent urinary diversion produces good longterm results (12)(13)(14) and, compared with traditional incontinent urostomy, provides a more attractive alternative for patients both from the social and the psychological viewpoint (12). Absence of odor and leakage are important qualities of a reservoir with adequate function, since such problems can give rise to Continent ileal urostomy (Kock reservoir) in children and adolescents isolation, depression, anxiety and limitation of various activities (11).…”
Section: Discussionmentioning
confidence: 99%
“…In two retrospective studies similar results were obtained, except that patients with a conduit reported more problems with their bathing habits [76,77]. None of the three published retrospective studies showed a difference between continent cutaneous diversion compared with orthotopic diversions [78][79][80]. With all instruments, the function of different diversions, expectations and quality of life remains very difficult to assess.…”
Section: Quality Of Lifementioning
confidence: 73%
“…Retrospektif yapılmış olan 3 çalışmada yaşam kaliteleri arası fark bulunmamıştır (52,53,54). Weijerman'ın 56 hastada 3 değişik diversiyon tekniği ile yaptığı çalışmada genelde benign hastalığı olan olgular kullanılmış.…”
Section: Ortotopik Mesane Ve Kutaneöz Kontinan Diversiyonunclassified
“…Bunlarda daha çok işeme ve inkontinansa yönelik sorgulama yapılmış ve fark olmadığı saptanmış (54). Sullivan'ın yaptığı 55 hastalık çalışmada sadece 10 hastaya kutaneöz diversiyon uygulanmış ve heriki grupta farklı olmayan ve oldukça iyi yaşam kalitesi bildirilmiştir (53). Mansson'un yaptığı nispeten daha yeni çalışmada FACT-BL ve hastane depresyon skalası kullanılmış ve fark bulunmamıştır (55).…”
Section: Ortotopik Mesane Ve Kutaneöz Kontinan Diversiyonunclassified